Workshop: Applying the Women’s Empowerment in Agrifood Governance (WEAGov) tool to support gender-responsive policy innovation across Africa - Kyle, Jordan; Ragasa, Catherine; Kaaria, Susan; Mangheni, Margaret; Odongo, Dorine; Omamo, Anne (International Food Policy Research Institute, 2024)
Well-designed and well-implemented agrifood policies can play a significant role in closing gender gaps and setting countries on a pathway toward sustainable and equitable food systems. IFPRI’s new Women’s Empowerment in Agrifood Governance (WEAGov) assessment tool—developed with support from the CGIAR research initiative on Gender Equality—measures women’s voice and agency in national-level policymaking in the agrifood sector (Figure 1). Identifying gaps in women’s voice in the agrifood policy process and finding entry points for inclusive participation are crucial to efforts to addressing gender inequities in agrifood systems—and to achieving the Sustainable Development Goals.